Moral motive selection in the lying dictator game - Kai Barron; Robert Stüber; Roel Van Veldhuizen (Lund University, School of Economics and Management, Department of Economics, 2022)
An extensive literature documents that people are willing to sacrifice personal material gain to adhere to a moral motive. Yet, less is known about what happens when moral motives are in conflict. We hypothesize that individuals engage in what we term "motive selection," namely adhering to the moral motive that aligns with their self-interest. We test this hypothesis using a laboratory experiment that induces a conflict between two of the most-studied moral motives: fairness and truth-telling. In line with our hypothesis, our results show that individuals prefer to adhere to the moral motive that is more aligned with their self-interest.
Keywords: C91; D01; D63; D90; 330; Motivated reasoning; dictator game; lying game; motives; moral dilemmas